Kawasaki Disease and Systemic Juvenile Idiopathic Arthritis – Two Ends of the Same Spectrum - Go, Ellen; van Veenendaal, Mira; Manlhiot, Cedric; Schneider, Rayfel; McCrindle, Brian W.; Yeung, Rae S. M. (Frontiers in Pediatrics, 2021)
Kawasaki disease (KD) and systemic juvenile idiopathic arthritis (sJIA) are two distinct systemic inflammatory diseases of childhood. Each diagnosis is based on criteria, but numerous clinical features are overlapping. As no specific diagnostic tests are available, differentiation between both disease entities can be challenging. Here, we describe the disease course of patients with co-diagnosis of both KD and sJIA (KD/sJIA). All our KD (n=1765) and sJIA (n=112) cases were critically reviewed for co-diagnosis of KD/sJIA. Eight KD/sJIA cases were identified and their clinical presentation, treatment regimens, coronary artery outcome and complications are herein described. Each KD/sJIA patient fulfilled diagnostic criteria for KD and for sJIA. Ongoing fever, rash and arthritis were present in each patient. The KD/sJIA patients had recalcitrant KD requiring multiple doses of intravenous immunoglobulin and steroids. Five patients had coronary artery dilatation at KD diagnosis, which resolved in all by 6 weeks. Pericardial effusion was present in 5 patients. One KD/sJIA patient developed macrophage activation syndrome. In conclusion, a small proportion (0.5%) of our KD patients evolved into sJIA, and 7% of our sJIA population presented initially as KD. KD/sJIA patients were characterized by a recalcitrant KD course and a high prevalence of coronary artery dilatation. Patients with co-diagnoses may provide a clue to potentially shared immunopathology in KD and sJIA, leading us to posit that both entities may be part of the same clinical spectrum.